Cardiovascular safety of non-insulin pharmacotherapy for type 2 diabetes - Xu, James (Cardiovasc Diabetol, 2017)
Patients with type 2 diabetes mellitus have a twofold increased risk of cardiovascular mortality compared with non-diabetic individuals. There is a growing awareness that glycemic efficacy of anti-diabetic drugs does not necessarily translate to cardiovascular safety. Over the past few years, there has been a number of trials evaluating the cardiovascular effects of anti-diabetic drugs. In this review, we seek to examine the cardiovascular safety of these agents in major published trials. Metformin has with-stood the test of time and remains the initial drug of choice. The sulfonylureas, despite being the oldest oral anti-diabetic drug, has been linked to adverse cardiovascular events and are gradually being out-classed by the various other second-line agents. The glitazones are contraindicated in heart failure. The incretin-based drugs have been at the fore-front of this era of cardiovascular safety trials and their performances have been reassuring, whereas the meglitinides and the alpha-glucosidase inhibitors still lack cardiovascular outcomes data. The sodium glucose cotransporter-2 inhibitors are an exciting new addition that has demonstrated a potential for cardiovascular benefit. Many of the currently available oral anti-diabetic agents have clinically relevant cardiovascular effects. The optimal approach to the reduction of cardiovascular risk in diabetic patients should focus on aggressive management of the standard cardiovascular risk factors rather than purely on intensive glycemic control.